Design and Simulation of a 3 GHz Rectangular Microstrip Patch Antenna Using ADS - ABUDRBALA, Hanan (Journal of Pure & Applied Sciences, 2025)
This study presents the design, simulation, and performance analysis of a rectangular microstrip patch antenna (RMPA) intended for wireless communication systems operating at 3 GHz. The antenna is modelled using Advanced Design System (ADS) software and fabricated on a RO4360 substrate with a dielectric constant of 6.15 and a thickness of 1.524 mm. The RO4360 material is selected due to its low loss, high-frequency stability, and compactness at microwave frequencies. To ensure proper impedance matching, an inset-fed microstrip line technique is employed. Simulation results demonstrate a return loss of -24.735 dB at 3.019 GHz and a fractional bandwidth of 1.2%, satisfying the bandwidth target for narrowband applications. Due to the single patch configuration, the radiation pattern is nearly omnidirectional with modest gain. The paper also reviews various enhancement techniques—such as feeding optimization, substrate modification, use of parasitic elements, and defected ground structures—to overcome limitations in bandwidth and gain. The proposed antenna design is suitable for compact and cost-effective wireless devices.